Pengaruh Investasi PMDN, PMA, dan Penyerapan Tenaga Kerja Terhadap Pertumbuhan Ekonomi dan Jumlah Penduduk Miskin Kabupaten/Kota di Provinsi Kalimantan Barat - Agustini, Yetty; Panca Kurniasih, Erni (Fakultas Ekonomi dan Bisnis, UNTAN, 2017)
The purpose of the research is to know the influence of domestic investment, foreign investment, and the absorption of labor toward the local economic growth and the amount of people who live in poverty in regency/city in West Kalimantan. This study tested 6 (six) years data, from 2008 to 2013 using panel data in the form of time series data (2008-2013) and cross section (10 countries/ cities) in the West Kalimantan province. Data were analyzed using regression analysis via Eviews 6.0. The results of the research showed that: 1) Domestic Investment influnces positively and significant toward the growth of local economic in regency/city in West Kalimantan. 2) Foreign Investment influences positively and significant toward the growth of local economic in regency/city in West Kalimantan. 3) The Absorption of labor influences positively and is significant toward the amount of local economic growth in regency/city in West Kalimantan. 4) Economic growth influences negatively and significant toward the amount of people who live in poverty in regency/city in West Kalimantan